Understanding the poverty-reducing livelihoods of child support grant caregivers in Riebeeck East, South Africa - Chikukwa, Vimbainashe (Rhodes University, Faculty of Humanities, Department of Sociology, 2015)
In 1994, racial domination in the form of apartheid ended in South Africa and the first postapartheid government was elected through a non-racial and democratic franchise. The new government inherited an entrenched system of racial inequality as well as widespread poverty amongst the formerly oppressed population, and it sought to address these challenges through policies of redistribution based on a new progressive constitution which emphasised the realisation of socio-economic rights. At the same time, and despite its redistributive measures, the post-apartheid government has pursued a macro-economic strategy with pronounced neoliberal dimensions. One of its critical redistributive measures focuses on social assistance to poor blacks, and this has entailed the construction and expansion of a massive social grant system including the child support grant which is received by millions of black South Africans on a monthly basis. The objective of this thesis is to examine and understand the livelihoods of child support grant recipients (or caregivers) in the context of conditions of extreme vulnerability marked by poverty. It does so by focusing on the small town of Riebeek East located in the Eastern Cape Province of South Africa. Though undoubtedly child support grant caregivers are victims of poverty, the thesis demonstrates that they are not without agency. They exist in structural conditions of vulnerability and poverty, but they nevertheless seek to manoeuvre and negotiate their way in and through their conditions of existence. This does not necessarily alleviate their poverty in any significant manner but it does show evidence of reflexivity, decision-making and responsibility in the pursuit of livelihood practices and outcomes. In making this argument, I draw upon the mega-theory of Margaret Archer (specifically, her morphogenetic approach) and the more middle-level perspective of the Sustainable Livelihoods Framework. Beyond contributing to the prevailing academic literature on the child support grant in South Africa, this thesis also hopefully makes a small contribution to controversies about structure and agency within sociology.
Keywords: Archer, Margaret Scotford -- Political and social views; Child caregivers -- South Africa -- Riebeek-Oos; Public welfare -- South Africa -- Riebeek-Oos; Grants-in-aid -- South Africa -- Riebeek-Oos; Poverty -- South Africa -- Riebeek-Oos; Critical realism; South Africa -- Social conditions -- 1994-; South Africa -- Economic conditions -- 1991-